The impact of artificial intelligence use on the e-commerce in Romania - Adrian Micu; Angela-Eliza Micu; Marius Geru; Alexandru Căpățînă; Mihaela-Carmen Muntean (Amfiteatru Economic Journal, 2021)
This study aims at identifying the tools used in e-commerce, able to optimize marketing campaigns. Managerial and marketing processes have been identified in the relevant body of knowledge that can be optimized using artificial intelligence; thus, a questionnaire has been designed within a quantitative research. The sample used in the research consists of 201 persons having managerial positions, who are involved in e-commerce, their companies' have been their company active in 2020, with at least one employee. The article highlights the managerial tools used in promoting products in the online environment and business processes that they want to optimize using artificial intelligence. At the same time, for the quantitative study, three hypotheses have been tested to identify the motivation to buy online, as well as the methods used by online store managers in the communication process. The limitations of this study are determined by the fact that only the managerial perspective is analysed, without considering the perception of the final consumer, which could have ethical implications. Optimizing the flow of stocks and logistics processes will be the subject of future research considering that it is the main challenge for management, as the quantitative research proved.
Keywords: M31; M15; O33; 330; e-commerce; m-commerce; artificial intelligence; marketing automation